Food Safety Training: A Study of Food Handlers Working in Hotels in the North of Jordan - Habiballah, Ma’moun A.; Al-Shakhsheer, Firas J.; Al-Sabi, Samer M.; Masadeh, Mousa A. (European Scientific Journal, ESJ, 2018)
In spite of decenniums of advancement, a numerous foodborne outbreaks continue to occur each year; these were mostly happening due to malpractices of employees working in foodservices. This study aims to investigate the role of food safety training in improving food handlers’ practices through the application of Knowledge, Attitude and Practices (KAP) model. Primary data were collected using a self-completed questionnaires that were collected from 100 Food and Beverage (F&B) employees working in hotels at the north of Jordan. Findings confirmed the role of food safety training in increasing F&B employeesâ€™ knowledge which positively correlates with their food handling practices. Furthermore, this study explored work environment elements affecting the transformation of learned knowledge into proper food handling practices; these include management motivation, availability of necessary resources and facilities and reinforcement programs. The study contributed to knowledge by employing the aforementioned variables to produce an adapted version of the KAP model.